Quantifying walking speeds in relation to ankle biomechanics on a real-time interactive gait platform: a musculoskeletal modeling approach in healthy adults - Peiffer, M.; Duquesne, K.; Delanghe, M.; Van Oevelen, A.; De Mits, S.; Audenaert, E.; Burssens, A. (Frontiers in Bioengineering and Biotechnology, 2024)
Background Given the inherent variability in walking speeds encountered in day-to-day activities, understanding the corresponding alterations in ankle biomechanics would provide valuable clinical insights. Therefore, the objective of this study was to examine the influence of different walking speeds on biomechanical parameters, utilizing gait analysis and musculoskeletal modelling.Methods Twenty healthy volunteers without any lower limb medical history were included in this study. Treadmill-assisted gait-analysis with walking speeds of 0.8 m/s and 1.1 m/s was performed using the Gait Real-time Analysis Interactive Lab (GRAIL ® ). Collected kinematic data and ground reaction forces were processed via the AnyBody ® modeling system to determine ankle kinetics and muscle forces of the lower leg. Data were statistically analyzed using statistical parametric mapping to reveal both spatiotemporal and magnitude significant differences. Results Significant differences were found for both magnitude and spatiotemporal curves between 0,8m/s and 1,1 m/s for the ankle flexion (p <0.001), subtalar force (p < 0.001), ankle joint reaction force and muscles forces of the M. Gastrocnemius, M. Soleus and M. Peroneus longus (𝛼 = 0.05). No significant spatiotemporal differences were found between 0,8 m/s and 1,1 m/s for the M. Tibialis Anterior and Posterior.Discussion A significant impact on ankle joint kinematics and kinetics was observed when comparing walking speeds of 0.8 m/s and 1.1 m/s. The findings of this study underscore the influence of walking speed on the biomechanics of the ankle. Such insights may provide a biomechanical rationale for several therapeutic and preventative strategies for ankle conditions.